USTART® - Othman, R.Y. (University of Malaya, 2015)
A programme organized by University of Malaya through its Centre of Innovation and Commercialization UMCIC, showcasing technology startups, interactive panel discussion from experts in university technology transfer and providing business networking and investor matching opportunities that will allow for a free flow exchange of best practices for research commercialization. The event aims to highlight efforts by universities in innovating and commercializing R&D outputs through the establishment of startup companies.The objectives are to build a University STARTUP COMMUNITY across universities, creating a showcase platform for regional excellence in university entrepreneurship, opening regional markets through inter-university joint venture, creating new opportunities through a Blue Ocean Strategy of shared mentoring and co-incubator facilities, student entrepreneurship initiatives and open up channels for startups through real angels and venture funders. This trademark registered under class 16, 35, 36, 38, 41 and 42